A stage-based model of design teaching. Issue 2 (1st December 2014) - Beier, Sofie
With a focus on the teaching of design students in higher education, the article will present a teaching approach model that follows the stages of the design process. The model suggests that at the Definition stage, the supervisor can focus on leading the student into a more thorough elaboration of the design problem; at the Analysis stage, the supervisor can facilitate a controlled structure of what needs to be investigated by taking on the role of a caring guide; at the Creating stage the supervisor can ask questions that reveal alternative angles; and at the Form Making stage the supervisor can apply an approach inspired by the master–apprentice relationship, where the student learns by observing the master at work.